Correlation between laboratory and field core stability tests and their link with performance and acl injury risk - Weber, T.; Mornieux, G.; Jacquot, R.; Gauchard, G.; Duchene, Y. (ISBS Proceedings Archive: Vol. 42: Iss. 1, 2024)
The purpose of this study was to identify the most relevant field tests for assessing core stability components and performance and injury risk. National-level women handball players (n=14) performed core stability tests in laboratory and field conditions. Moreover, their athletic performance and ACL injury risk were assessed. CKCUEST was explained by flexibility and endurance component of core stability. Shooting speed was correlated with force, flexibility and endurance, while jumping height was linked to flexibility. Positive correlation was found between ACL injury risk and core strength. These findings could help trainers to select more discriminant tests to evaluate their athletes.